Unveiling multiple AGN activity in galaxy mergers. Issue 2 (22nd March 2017) - De Rosa, A.; Bianchi, S.; Bogdanović, T.; Decarli, R.; Heidt, J.; Herrero‐Illana, R.; Husemann, B.; Komossa, S.; Kun, E.; Loiseau, N.; Guainazzi, M.; Paragi, Z.; et al.
Abstract : In this paper we present an overview of the MAGNA (Multiple AGN Activity) project aiming at a comprehensive study of multiple super‐massive black hole systems. With the main goal of characterizing the sources in merging systems at different stages of evolution, we selected a sample of objects optically classified as multiple systems on the basis of emission line diagnostics and started a massive multiband observational campaign. Here we report on the discovery of the exceptionally high active galactic nuclei (AGN) density compact group SDSS (Sloan Digital Sky Survey) J0959+1259. A multiband study suggests that strong interactions are taking place among its galaxies through tidal forces, and therefore this system represents a case study for physical mechanisms that trigger nuclear activity and star formation. We also present a preliminary analysis of the multiple AGN system SDSS J1038+3921.